Training uneven parallel bar back salto dismounts - Pidcoe, P. E. (Technique, 2001)
This paper was written in an effort to describe some of the basic biomechanical issues surrounding the training and performance of uneven parallel bar back salto flyaway dismounts. The dismount is common in gymnastics and is seen first in Level 6 compulsory competition. This dismount involves fundamentals for many higher-level dismounts and release moves.